“Seek the peace of the city” (Jer 29,7) Church practice after the serious case of public welfare-oriented probation in the pandemic - Beck, Wolfgang (Studia Theologica Varsaviensia, 2022)
During the corona pandemic, pastoral practice and church proclamation show structural problems as well as new beginnings. The question is whether effects for a dynamic church development will emerge from them in order to find a stronger orientation of pastoral action towards the common good. Which social players enjoy priority and which areas of society are considered "nice to have" and thus dispensable, at least in times of crisis? This question pervades public debates throughout the multiple waves of the Corona pandemic: prioritising the allocation of vaccination appointments, prioritising the opening of shops and facilities, and prioritising the allocation of aid money and Corona Relief funds. Behind these decisions is the question of who is considered systemically important in modern societies and from whom contributions to the common good are to be expected.